Thunderstorm Algorithm for Determining Unit Commitment in Power System Operation - Afandi, A.N.; Sulistyorini, Yunis (Journal of Engineering and Technological Sciences, 2016)
Solving the unit commitment problem is an important task in power system operation for deciding a balanced power production between various types of generating units under technical constraints and environmental limitations. This paper presents a new intelligent computation method, called the Thunderstorm Algorithm (TA), for searching the optimal solution of the integrated economic and emission dispatch (IEED) problem as the operational assessment for determining unit commitment. A simulation using the IEEE-62 bus system showed that TA has smooth convergence and is applicable for solving the IEED problem. The IEEDâs solution is associated with the total fuel consumption and pollutant emission. The proposed TA method seems to be a viable new approach for finding the optimal solution of the IEED problem.